Agricultural Settlement Patterns in Upper Canada, 1782-1851: A Simulation Analysis - Norton, William (My University, 1974)
This study of agricultural settlement patterns in Upper Canada, 1782-1851, has two principal aims. They are the isolation of variables relevant to a settler's decision to locate and the production of patterns for years between 1782 and 1851. Data are available for 1782 and 1851 so that these patterns are known; data for years between 1782 and 1851 are limited. Considerations of available pertinent literature and of the settlement history of Upper Canada suggest several principal variables; namely, availability of agricultural lots, distance from entry point, land quality for agriculture and potential in relation to market centres. These four variables are incorporated into a model of the settlement process which is probabilistic and is opaerationalised by means of simulation. The township is the scale of analysis. On the basis of the variables, attractiveness values are calculated for each township and interpreted as the porbability of receiving a settler.
Patterns are produced for 1851 and for years between 1782 and 1851. These model outputs are compared to the available real world data. The two principal means of comparison are visual analysis of settlement maps and correlation analysis.
The four variables are shown to be relevant and exponent values for each variable are estimated. The following ranking is suggested:
1. Entry points
2. Land quality
3. Lot availability
4. Potential
It is also demonstrated that, for patterns before 1851, the surveying of townships is important, although the effects of this factor are not evident in 1851.
This research, then, is an excursion into a relatively new field of historical geography - the creation of theoretical worlds of the past. Comparison of theoretical and real worlds indicates that the model formulated is appropriate. Further, because the model is quite general it is thought that it might be relevant for other areas and other times.
Keywords: Geography; Geography